Epistemic Trust and the Emergence of Conduct Problems: Aggression in the Service of Communication - Talia, Alessandro; Duschinsky, Robbie; Mazzarella, Diana; Hauschild, Sophie; Taubner, Svenja (Frontiers in Psychiatry, 2021)
Fonagy and colleagues have recently proposed that deficits in the capacity for epistemic trust (i.e. the expectation that interpersonal communication is relevant to the addressee) are fundamental to psychopathology. In this paper, we consider the implications of this hypothesis for understanding the role of aggression in conduct disorder and conduct problems more generally. Our main proposal is to view conduct problems not only as reflecting dysregulation, but as an adaptation that allows communication with others who are (or are perceived to be) unreliable. Our formulation hinges on two propositions. The first one is to view aggression as a modality of communication adapted to scenarios in which the communicator expects the audience to have low epistemic trust in the communicator. The second idea is to conceptualize the failed “unlearning of aggression” as reflecting a lack of interest in maintaining one’s reputation as a communicator, which in turn stems from a lack of epistemic trust in other communicators. In this paper, we discuss these ideas and examine how they may account for the developmental pathways that lead young people to develop conduct problems.